Isolated Amylase Deficiency in Children and Its Clinical Implication. Issue 6 (June 2019) - Hopson, Puanani; Patel, Samit; Bornstein, Jeffrey; Mehta, Devendra; Horvath, Karoly
ABSTRACT: Objectives: Among the 3 lines of pancreatic enzymes, amylase secretion develops last and it is not detected in duodenal aspirates of infants in the first month after birth. The aim of this study was to assess the prevalence and symptoms of isolated amylase deficiency in children. Methods: During a 6-year period, we performed endoscopic pancreatic function tests (ePFT) in 712 children. Isolated amylase deficiency was defined as activity that was below the third percentile of our referenced population with normal lipase and protease activities. Results: Seventy-two children between age 0.21 and 15.7 years (boys, n = 35) had isolated amylase deficiency. The highest prevalence of isolated amylase deficiency was found in patients less than 6 months of age (52.9%). From 6 months to 1 year of age, the prevalence was 40%. The prevalence gradually decreased until 18 months. Failure to thrive, poor weight gain, diarrhea, and abdominal bloating were the most frequent indications for ePFT. Eleven children had repeat ePFT after initial diagnosis and 6 had normal enzyme activity, whereas 5 had remained amylase-deficient an average of 1.65 years later. Conclusions: The prevalence of selective amylase deficiency was 10.1% in the 712 children who underwent ePFT with the suspicion of malabsorption. Low amylase activity is "physiologic" in infants <6 months of age, however, this study supports that it should be considered in the differential diagnosis in children older than 6 months of age.